Character Education on the Hindu Religious Education in Elementary Schools - Kiriana, I Nyoman; Okta Priantini, Dewa Ayu Manu (International Journal of Elementary Education, 2021)
The problem behind this research was the lack of inculcation of character values among students. This research aims to analyze the implementation of character education in the learning process of Hindu religious education. This type of research was qualitative using a qualitative descriptive approach. The subjects in this research were elementary school teachers and students. Data collection techniques used in this research were observation, interviews and documentation. The data analysis method used was in the form of qualitative descriptive analysis, namely the process of systematically searching and compiling data obtained from interviews, field notes, and documentation, by organizing data into categories, breaking down into units, synthesizing, compiling into patterns, choosing which ones are important, and which will be studied, and making conclusions so that they are easily understood by themselves and others. Based on the result of this research and discussion described, it can be concluded that the implementation of character education was only able to find 14 characters. The character values achieved consist of 18 character values in the development of cultural and national character education by the Ministry of Education and Culture so that it can be concluded that the inculcation of values has been carried out well even though it was still maximal.